VD_FINDINFO HC / 2012 / 164 vom 14. Mai 2012 - VD Tribunal cantonal (2012)
CONTRAT DE TRAVAIL, INDEMNITÉ DE VACANCES, DILIGENCE, FIDÉLITÉ, RÉSILIATION, SALAIRE | 321a al. 3 CO, 321a CO, 321e al. 1 CO, 321e CO, 322 CO, 329d al. 1 CO, 329d al. 2 CO, 329d al. 3 CO, 329d CO, 82 CO